2018
DOI: 10.15739/ijapr.18.013
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cross River State is endowed with natural and cultural resources. Most of these resources are yet to be developed for tourist appreciation. The study aimed to assess the prospects of community-based ecotourism (CBE) and stakeholder's involvement in ecotourism development in Iko Esai Community, Cross River State, Nigeria. Multistage sampling method was adopted for the study. Using 5.57% sampling intensity, 150 structured questionnaires were administered to two randomly sampled wards for data collection. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The Oban forest is also part of the "Gulf of Guinea biodiversity hotspots of conservation concerns" in West Africa (Agaldo et al, 2016). It is known to house a large number of endemic flora and fauna species (Oates et al, 2004), including most of the 935 tree species identified in Nigeria (Lock & Keay, 1991), other herbaceous plant species, and a rich diversity of butterflies, birds, reptiles, amphibians, and a wide range of mammal species including ungulates, cats, buffalo, elephants, and primates, including the world's rarest lowland gorillas and others plant and animal species (Asuk et al, 2018).…”
Section: Study Locationmentioning
confidence: 99%
“…The Oban forest is also part of the "Gulf of Guinea biodiversity hotspots of conservation concerns" in West Africa (Agaldo et al, 2016). It is known to house a large number of endemic flora and fauna species (Oates et al, 2004), including most of the 935 tree species identified in Nigeria (Lock & Keay, 1991), other herbaceous plant species, and a rich diversity of butterflies, birds, reptiles, amphibians, and a wide range of mammal species including ungulates, cats, buffalo, elephants, and primates, including the world's rarest lowland gorillas and others plant and animal species (Asuk et al, 2018).…”
Section: Study Locationmentioning
confidence: 99%